Clinical Experience of Kawasaki Disease in Two Tertiary Care Centers in Jeddah, Saudi Arabia - Hussain A. Alsaggaf (Journal of King Abdulaziz University: Medical Sciences, 2023)
To analyze the clinical presentation, investigations, diagnosis and management of patients with Kawasaki disease seen at the two centers, an analytic study of data from the medical records of all patients of Kawasaki disease admitted to King Abdulaziz University Hospital and King Faisal Specialist Hospital and Research Centerwas done from January 2000 to June 2012. A total of 56 patients were included in the study with the mean age of 30.5 months (range from 2-132 months). Diagnosis and administration of intravenous immunoglobulin were performed after the mean of 8.4 days (ranged from 3-31 days). Twenty-eight patients had classical Kawasaki disease (50%) while the other 28 had incomplete Kawasaki disease (50%). A wide variety of clinical symptoms and signs were found in our patients. Thrombocytosis was detected in 32 patients at presentation. Coronary artery lesion was detected in 27 patients; 13 from classical Kawasaki disease group and 14 from incomplete Kawasaki disease group. Out of these, 20 had thrombocytosis at presentation, making it a significant risk factor for the development of coronary artery lesion (p-value = 0.013). The percentage of incomplete Kawasaki disease is quite high in our patients. Epidemiological studies are needed, and National Kawasaki Disease Awareness Program, aiming at avoiding delays in diagnoses, is suggested.